ANALISIS PENGARUH CITRA PRODUK TERHADAP KEPUTUSAN PEMBELIAN SABUN CUCI PAKAIAN RINSO PADA MAHASISWA/I PERGURUAN TINGGI DI BOGOR - Argya, Mohammad (Al-Infaq: Jurnal Ekonomi Islam, 2018)
The purpose of this study is to know how big the influence of Brand Image Detergent Rinso of purchase decision on students of STEI Tazkia, Pakuan University and Djuanda University in Bogor. The method used in this study is multiple regression methods to see the influence of the Brand Image of Detergent Rinso purchase decisions and use the correlation coefficient to see how much the influence brand image of Detergent Rinso purchase decision on students of STEI Tazkia, Pakuan University and Djuanda in Bogor. Based on the analysis, known that the influence of the Brand Image of Detergent Rinso purchase decisions classified as strong enough seen from the values of r = 0,642. In addition, based on the calculated correlation coefficient demonstrate the value of rsquare =0,412, shows that for 41,2% purchasing of Detergent Rinso are influenced by a Brand Image while the remaining 58,8% influenced by other factors is not examined.